2015
DOI: 10.1155/2015/652416
|View full text |Cite
|
Sign up to set email alerts
|

The Type III Secretion System (T3SS) ofChlamydophila psittaciIs Involved in the Host Inflammatory Response by Activating the JNK/ERK Signaling Pathway

Abstract: Chlamydophila psittaci (C. psittaci) is a human zoonotic pathogen, which could result in severe respiratory disease. In the present study, we investigated the role and mechanism of the type III secretion system (T3SS) of C. psittaci in regulating the inflammatory response in host cells. C. psittaci-infected THP-1 cells were incubated with the specific T3SS inhibitor INP0007, inhibitors of ERK, p38, or JNK, and the levels of inflammatory cytokines were analyzed using Q-PCR and ELISA. The levels of ERK, p38, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…ERK1/2 are activated by MAP/ERK1/2 kinases 1 and 2 (MEK1/2) by dual phosphorylation at their threonine 202 and tyrosine 204 residues ( Cagnol and Chambard, 2010 ). Activated ERK1/2 and SAPK/JNK can directly phosphorylate a variety of cytoplasmic and nuclear substrates involved in various cellular processes such as proliferation, differentiation, apoptosis and survival ( He et al., 2015 ; Meng et al., 2019 ; Sharma et al., 2019 ). p38 protein kinase is a tyrosine phosphoprotein kinase associated with inflammation and growth factor responses ( Mo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…ERK1/2 are activated by MAP/ERK1/2 kinases 1 and 2 (MEK1/2) by dual phosphorylation at their threonine 202 and tyrosine 204 residues ( Cagnol and Chambard, 2010 ). Activated ERK1/2 and SAPK/JNK can directly phosphorylate a variety of cytoplasmic and nuclear substrates involved in various cellular processes such as proliferation, differentiation, apoptosis and survival ( He et al., 2015 ; Meng et al., 2019 ; Sharma et al., 2019 ). p38 protein kinase is a tyrosine phosphoprotein kinase associated with inflammation and growth factor responses ( Mo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MAPKs can cooperate with other signal transduction pathways, including that of the transcriptional regulator nuclear factor-κβ (NF-κβ), which regulates the transcription of genes important for cytokine and chemokine production, including interleukin IL-6, IL-8, IL-12, and tumor necrosis factor-α [ 16 , 17 , 18 ], as well as the anti-apoptotic factor Bcl-2 [ 17 , 19 ]. Phosphorylation of MAPKs leads to activation or inhibition of transcription factors [ 15 , 20 ], resulting in up- or down-regulation of important immune factor genes that regulate bacterial infections in the host [ 13 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IL-6, IL-8, and MCP-1 have been identified as the key factors for induction and are involved in various inflammatory diseases, which are also associated with the severity of inflammatory diseases ( Deshmane et al, 2009 ; Klapproth and Sasaki, 2010 ; Kanmani et al, 2019 ). Previous studies revealed that C. psittaci stimulated various inflammatory factors in monocytes ( He et al, 2015 ). In addition, infection with C. psittaci could also upregulate inflammatory mediators such as IL-6 and IL-8 in different cells containing the cervical epithelioid carcinoma HeLa cell line and the cervical squamous carcinoma SiHa cell line ( He et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that C. psittaci stimulated various inflammatory factors in monocytes ( He et al, 2015 ). In addition, infection with C. psittaci could also upregulate inflammatory mediators such as IL-6 and IL-8 in different cells containing the cervical epithelioid carcinoma HeLa cell line and the cervical squamous carcinoma SiHa cell line ( He et al, 2015 ). Moreover, in vitro studies have shown that MCP-1 can be produced in the human endothelial cells after chlamydial infection, which is a leading contributor of atherosclerotic lesions characterized by monocyte infiltration ( Molestina et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%